P-72 Memory first – a primary care based holistic service. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Hodges, Emma; McCartney, Jeanette; Greaves, Nicola
Abstract : The aim of the Memory First service was to scale up a memory service from a single pilot GP practice to 41 practices across two commissioning localities. The new partnership between a local GP Federation and two hospices aims to deliver a holistic service, tackle unmet need and improve EOLC for people with dementia. A standardised service design was implemented across all practices. A key role in the service delivery is the new role of a non-clinical Care Facilitator (CF). The hospices employ, train and manage the CF element of the service. The CFs have an honorary contract with allocated GP Practices enabling them to access/update records as part of the primary care team. The CF undertakes a holistic assessment and conducts the General Practitioner Assessment of Cognition (GPCOG). The CF decides whether to book the patient into a memory clinic which is held in primary care and/or signposts, organises other services to meet needs from the assessment such as falls, social care, carer support, social groups etc. Since January 2014 to end of August 2014, 1273 patients have been referred to the service, 859 have received a holistic assessment by a hospice employed CF. 37% have required attendance at a memory clinic for diagnosis, of the patients who have completed the pathway just under 50% of patients attending clinic receive a formal diagnosis of dementia. This pilot has enabled the launch of our Hospice Dementia strategy.